Chemical Constituents And Bioactivities Of Clausena Excavata - Muhamad Sharif, Nurul Waznah (2009)

(untitled)
Clausena excavata (Rutaceae) which is locally known as “Pokok Kemantu”(ghostly tree) or “Pokok Cemamar” (diarrhoea tree) is one of the Malaysian species of ulam with high anti-oxidant properties. This plant is used in folk medicine for treating ailments like colic, cough, wounds, rhinitis, and stomach trouble, fever and as a tonic. Detail investigations on the leaves, stem bark and roots of Clausena excavata (Rutaceae) resulted in the isolation of nine compounds. These compounds are from several groups of secondary metabolites such as limonoids, carbazole alkaloids, coumarins, and triterpenes. The structures of these compounds were elucidated using spectroscopic techniques such as NMR, GCMS, and IR and also by comparison with previously reported data.The stem bark of Clausena excavata which was collected from Jabi and Pendang, Kedah in December 2006 , yielded a new limonoid, clausenolide 1-methylether (133). This was obtained from the methanol extract together with a known limonoid, clausenarin (8). Besides that, two carbazole alkaloids, clausine–K (43) and 3-formyl-2,7- dimethoxycarbazole (126) were isolated from the crude chloroform extract and two triterpenes, stigmasterol (131) and β-sitosterol (132) were isolated from the hexane extract. Similar work on the roots led to the isolation of three known coumarins which were identified as xanthyletin (64) and dentatin (130), together with one carbazole alkaloid, nordentatin (54). The crude extracts and pure compounds of Clausena excavata were subjected to cytotoxic activity test. The activities were expressed in terms of fifty percent inhibition concentration (IC50) against HL60 cancer cell line (Human promyelocytic leukemia), MCF-7 cancer cell line (Human breast cancer), HT-29 cancer cell line (Human colon cancer), and HeLa cancer cell line. It was found that the crude hexane, chloroform, and acetone extracts exhibited very strong activities against HL-60, and MCF-7 cell lines with IC50 values < 6μg/mL. However, the new limonoid, clausenolide 1-methylether (133) and clausenarin (8) which were isolated from the methanol extract of stem bark showed no significant cytotoxicity against all the cancer cell lines with IC50 value >30μg/mL as compared to another 2 isolated compounds, xanthyletin (64) and dentatin (130) .